Global projections of river flood risk in a warmer world. Issue 2 (14th February 2017) - Alfieri, Lorenzo; Bisselink, Berny; Dottori, Francesco; Naumann, Gustavo; de Roo, Ad; Salamon, Peter; Wyser, Klaus; Feyen, Luc
Abstract: Rising global temperature has put increasing pressure on understanding the linkage between atmospheric warming and the occurrence of natural hazards. While the Paris Agreement has set the ambitious target to limiting global warming to 1.5°C compared to preindustrial levels, scientists are urged to explore scenarios for different warming thresholds and quantify ranges of socioeconomic impact. In this work, we present a framework to estimate the economic damage and population affected by river floods at global scale. It is based on a modeling cascade involving hydrological, hydraulic and socioeconomic impact simulations, and makes use of state‐of‐the‐art global layers of hazard, exposure and vulnerability at 1‐km grid resolution. An ensemble of seven high‐resolution global climate projections based on Representative Concentration Pathways 8.5 is used to derive streamflow simulations in the present and in the future climate. Those were analyzed to assess the frequency and magnitude of river floods and their impacts under scenarios corresponding to 1.5°C, 2°C, and 4°C global warming. Results indicate a clear positive correlation between atmospheric warming and future flood risk at global scale. At 4°C global warming, countries representing more than 70% of the global population and global gross domestic product will face increases in flood risk in excess of 500%. Changes in flood risk are unevenly distributed, with the largest increases in Asia, U.S., and Europe. In contrast, changes are statistically not significant in most countries in Africa and Oceania for all considered warming levels. Key Points: Global flood risk assessment at different warming levels based on ensemble climate projections At 4°C warming 70% of the world population and GDP will face increase in flood impact over 500% Projected changes in flood risk are largest in Asia, America, and Europe